THE MAIN FACTORS OF MUDFLOW FORMATION ON THE SLOPE AREAS OF THE CARPATHIANS - Hnativ, Ihor; Hnativ, Roman (SWorld-Ger Conference proceedings, 2025)
The earliest studies of mudslides in Ukraine were recorded at the end of the 19th century in Crimea. The occurrence of mudslides is usually periodic and depends on the accumulation of loose debris in areas prone to mudslides and the occurrence of dangero